2011
DOI: 10.1111/j.1462-2920.2011.02493.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial chemotaxis towards aromatic hydrocarbons in Pseudomonas

Abstract: Bacterial chemotaxis is an adaptive behaviour, which requires sophisticated information-processing capabilities that cause motile bacteria to either move towards or flee from chemicals. Pseudomonas putida DOT-T1E exhibits the capability to move towards different aromatic hydrocarbons present at a wide range of concentrations. The chemotactic response is mediated by the McpT chemoreceptor encoded by the pGRT1 megaplasmid. Two alleles of mcpT are borne on this plasmid and inactivation of either one led to loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 49 publications
1
64
0
Order By: Relevance
“…37). We have shown previously that the transfer of the mcpT gene to other species confers chemotaxis toward aromatic compounds, suggesting the establishment of functional signaling complexes between McpT and host proteins (38). The demonstration of efficient methylation of McpT by a foreign CheR methyltransferase is consistent with this suggestion and offers the possibility of "chemotactic engineering" of related strains by the transfer of chemoreceptor genes.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…37). We have shown previously that the transfer of the mcpT gene to other species confers chemotaxis toward aromatic compounds, suggesting the establishment of functional signaling complexes between McpT and host proteins (38). The demonstration of efficient methylation of McpT by a foreign CheR methyltransferase is consistent with this suggestion and offers the possibility of "chemotactic engineering" of related strains by the transfer of chemoreceptor genes.…”
Section: Discussionsupporting
confidence: 70%
“…McpS is encoded by the genome of P. putida KT2440, whereas McpT is a plasmid encoded receptor present in the strain P. putida DOT-T1E (60). The McpT receptor is of biotechnological relevance because it is responsible for the hyperchemotaxis phenotype toward aromatic toxic hydrocarbons such as toluene (38). It has been shown that there is a link between the degradation of aromatic hydrocarbons and FIGURE 12.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Responses to (methyl)phenols and phenylacetic acid are mediated through energy taxis via Aer2 (Luu et al, 2013;Sarand et al, 2008), whilst responses to naphthalene, 2-nitrobenzoate, toluene, 4-chloroaniline, catechol and aromatic amino acids are sensed by chemotaxis via specific MCPs (Grimm & Harwood, 1999;Iwaki et al, 2007;Lacal et al, 2011;Oku et al, 2012;Parales et al, 2000;Taguchi et al, 1997;Vangnai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%